Complications and Avoidance in Neurointerventional Surgery - Girish Rajpal; Noufal Basheer (Indian Journal of Neurosurgery)
Because neurointerventional surgery is a minimally invasive technique does not mean that it is qualified for complication-free procedures. Rather working about 2 m away from the three-dimensional (3D) target lesion and looking at two-dimensional (2D) images makes it one of the most complication-prone subspecialties. Advancement in hardwares, techniques, and technologies with continuous ability to learn and modify accordingly can only keep the complication rate low as compared with traditional vascular neurosurgery.